Immunomodulatory N-acyl Dopamine Glycosides from the Icelandic Marine Sponge Myxilla incrustans Collected at a Hydrothermal Vent Site - Einarsdottir, Eydis; Liu, Hong-Bing; Freysdottir, Jona; Gotfredsen, Charlotte Held; Omarsdottir, Sesselja (Planta Medica, 2016)
A chemical investigation of the sponge (Porifera) Myxilla incrustans collected from the unique submarine hydrothermal vent site Strytan, North of Iceland, revealed a novel family of closely related N-acyl dopamine glycosides. Three new compounds, myxillin A (1), B (2) and C (3), were isolated and structurally elucidated using several analytical techniques, such as HR-MS, 1D and 2D NMR spectroscopy. Myxillin A (1) and B (2)were shown to be structurally similar, composed of a dopamine moiety, but differ in the acyl chain length and saturation. The myxillin C (3) has a dehydrotyrosine moiety composing the same acyl chain and glycosylation as myxillin B (2). Myxillins A (1) and C (3) were tested for immunomodulating activity in an in vitro dendritic cell model. Dendritic cells matured and stimulated in the presence of myxillin A (1) secreted lower levels of IL-12p40, whilst dendritic cells matured and stimulated in the presence of myxillin C (3) secreted lower levels of IL-10 compared with dendritic cells matured and stimulated in the presence of the solvent alone. These opposing results indicate that the structural differences in the aromatic ring part of the molecules could have an impact on the immunological effects of dendritic cells. These molecules could, therefore, prove to be important in preventing inflammatory diseases on the one hand, and inducing a response to fight tumors and/or pathogens on the other hand. Further studies will be needed to confirm these potential uses.
Keywords: Porifera; sponges; Myxillidae; N-acyl dopamine glycosides; immunomodulation; dendritic cells; myxillin A, B, and C